THE INFLUENCE OF COVID 19 ON PATIENTS WITH OCCUPATIONAL ASTHMA - N. Dimitrova; S. Dermendzhiev (Trakia Journal of Sciences)
PURPOSE: The purpose of our presentation is to provide an overview of patients with COVID 19 and occupational asthma. Often we forget about the relationship between harmfulness in the workplace and the diseases they cause, as well as what risk factor they may be for other diseases. Occupational diseases can lead to severe disability and decreased quality of life. On the other hand, COVID 19 in some patients may proceed as a life-threatening condition. This review will pay attention to patients with asthma and COVID 19, paying particular attention to occupational asthma and risk factors of the working environment, as well as recommendations for working in pandemic conditions. METHODS: The diagnosis of asthma is made according to the following tests: spirometry is the recommended test to confirm this diagnose, the peak flow meter is and FeNO - a test to determine the level / content of nitric oxide in the exhaled air from the lungs, in patients with normal results from the abovementioned tests, but who had signs and symptoms of asthma, provocation tests may be performed. RESULTS: Patients with allergic asthma are more vulnerable to COVID-19 and the disease is more severe than in patients with the chronic pulmonary obstructive disease and non-allergic asthma. Older age and nonwhite ethnicity also appear to provide a higher risk of disease and its course within the population with asthma and COVID-19. CONCLUSION: There is still insufficient evidence to assess whether the risk of COVID-19 infection with asthma patients, including occupational asthma, is significantly higher.